Compromise and Synergy in High‐Efficiency Thermoelectric Materials. Issue 14 (6th March 2017) - Zhu, Tiejun; Liu, Yintu; Fu, Chenguang; Heremans, Joseph P.; Snyder, Jeffrey G.; Zhao, Xinbing
Abstract : The past two decades have witnessed the rapid growth of thermoelectric (TE) research. Novel concepts and paradigms are described here that have emerged, targeting superior TE materials and higher TE performance. These superior aspects include band convergence, "phonon‐glass electron‐crystal", multiscale phonon scattering, resonant states, anharmonicity, etc. Based on these concepts, some new TE materials with distinct features have been identified, including solids with high band degeneracy, with cages in which atoms rattle, with nanostructures at various length scales, etc. In addition, the performance of classical materials has been improved remarkably. However, the figure of merit zT of most TE materials is still lower than 2.0, generally around 1.0, due to interrelated TE properties. In order to realize an "overall zT > 2.0, " it is imperative that the interrelated properties are decoupled more thoroughly, or new degrees of freedom are added to the overall optimization problem. The electrical and thermal transport must be synergistically optimized. Here, a detailed discussion about the commonly adopted strategies to optimize individual TE properties is presented. Then, four main compromises between the TE properties are elaborated from the point of view of the underlying mechanisms and decoupling strategies. Finally, some representative systems of synergistic optimization are also presented, which can serve as references for other TE materials. In conclusion, some of the newest ideas for the future are discussed. Abstract : Enhancing the figure of merit zT is the central theme of thermoelectric research. The various recently proposed concepts and paradigms for optimizing thermoelectric properties are reviewed. Contradiction and compromise between the thermoelectric parameters and decoupling mechanisms are elaborated. Examples of synergistic optimization are given, highlighting typical efforts toward high‐performance thermoelectric materials.